UPAYA MARKETING HASIL INDUSTRI PEMBINAAN KEMANDIRIAN NARAPIDANA DI LEMBAGA PEMASYRAKATAN KELAS IIA TEMBILAHAN - Arvandio Meilvindra S; Mitro Subroto (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
The Class IIA Tembilahan Correctional Institution plays a role in determining the treatment of perpetrators of crimes from the prison system to the 1964 penitentiary system. The implementation employs two development programs, namely personality development and independence development. Class IIA Tembilahan Prison has various activities to promote self-sufficiency, from chicken farms and cattle farms to fish ponds, prison workshops and laundry provided for prison inmates so that inmates have the skills and experience to do things that are useful when they leave prison. Regarding the market to be targeted, a marketing strategy is needed that can increase the selling power of the products produced. Improvements ranging from product quality, product selling prices, product distribution, and product promotion. This paper seeks to draw conclusions about the right marketing strategy in an effort to increase the sales value of production from convicts. Marketing Optimization Efforts to Achieve Industry Results for the Development of Prisoners' Independence in Class IIA Tembilahan Correctional Institutions, which aims to reintegrate prisoners into society by optimizing marketing for the development of prisoners' independence. The results at the Tembilahan Class IIA prison can be a good first step and have a significant impact on the lives of inmates.